Familial nonmedullary thyroid carcinoma - clinical relevance and prognosis: a European multicenter study - Hillenbrand, Andreas; Varhaug, Jan-Erik; Brauckhoff, Michael; Pandev, Rumen; Haufe, Sabine; Dotzenrath, Cornelia; Köberle, Roswitha; Hoffmann, Rainer; Klein, Günther; Kadmon, Martina; Negele, Thomas; Hagieva, Tatjana; et al. (Langenbeck's archives of surgery, 2010)
Approximately 5% of differentiated thyroid carcinomas are of familial origin. These familial nonmedullary thyroid carcinomas (FNMTC) have an increased risk of multifocal disease and lymph node involvement. Consequently, higher recurrence rates and decreased disease-specific survival rates are described. The best surgical approach is discussed controversially.